Statistical Methods Applied to Space Weather Science - Telloni, Daniele (Frontiers in Astronomy and Space Sciences, 2022)
Space Weather is receiving more and more attention from the heliophysical scientific community, as it is now well established that an adequate capability of monitoring any Earth-directed heliospheric event and forecasting the most severe perturbations produced by solar activity and their impact on the geo-spatial environment is crucial, given the human increasing reliance on space-related technologies and infrastructures. Predicting how the Sun affects life on Earth and human activities in the short term relies on establishing empirical laws to forecast not only the arrival time on Earth of potentially geo-effective solar drivers, but also, and more importantly, the intensity of induced geomagnetic disturbance (if any). Scientific studies performed on a statistical basis are the key to providing such empirical laws and analytically relating solar-wind properties to geomagnetic indices. This paper summarizes the results achieved by the author in the last few years in the context of Space Weather science, and based on statistical analyses of interplanetary and geomagnetic data.